Discarding decisions: A behavioral analysis of consumer food waste in Indonesia - I Gede Agus Ariutama; Ram Pandit; Benedict White; Maksym Polyakov (Food Quality and Preference, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Genetic Features of Tongue Cancer Recurrence in Young Adults - E. S. Kolegova; A. A. Schegoleva; R. S. Vorobev; I. K. Fedorova; D. E. Kulbakin; A. P. Polyakov; A. V. Mordovsky; L. P. Yakovleva; A. S. Vyalov; V. T. Tsiklauri; M. A. Kropotov; N. G. Suchkova; et al. (Bulletin of Experimental Biology and Medicine, 2024)

Assessment of the Spatial Resolution and Accuracy of Temperature Measurements in Radiothermometry of the Breast - M. V. Polyakov; A. V. Khoperskov; S. V. Agasieva; I. O. Porokhov (Biomedical Engineering, 2023)

Differential Markers of Subpopulations of Epithelial Cells of the Larynx in Squamous Cell Carcinoma - I. V. Arutyunyan; A. G. Soboleva; K. B. Gordon; D. S. Kudashkina; D. A. Miroshnichenko; A. P. Polyakov; I. V. Rebrikova; A. V. Makarov; A. V. Lokhonina; T. Kh. Fatkhudinov (Bulletin of Experimental Biology and Medicine, 2022)

Exploring Five Methods for Estimating Net Community Production on the Siberian Continental Shelf and Slope of the Arctic Ocean - M. B. Alkire; I. Polyakov; R. W. Macdonald (Frontiers in Marine Science, 2022)
The loss of sea ice and changes to vertical stratification in the Arctic Ocean are altering the availability of light and nutrients, with significant consequences for net community production (NCP) and carbon export. However, a general lack of quality data, particular during winter months, inhibits our ability to quantify such change. As a result, two parameters necessary for calculating annual NCP, integration depth (Z int ) and pre-bloom nitrate concentration (N pre ), are often either assigned or estimated from summer measurements. Vertical profiles of temperature, salinity, nitrate, and dissolved oxygen were collected during three cruises conducted between August and October of 2013, 2015, and 2018 in a data-sparse region of the Arctic Ocean along the Siberian continental slope. Estimates of NCP were calculated from these data using five different methods that either assigned constant values for Z int and/or N pre or estimated these parameters from summer observations. The five methods returned similar mean values of Z int (44–54 m), N pre (5.4–5.7 mmol m –3 ), and NCP (12–16 g C m –2 ) across the study region; however, there was considerable variability among stations/profiles. It was determined that the NCP calculations were particularly sensitive to N pre . Despite this sensitivity, mean NCP estimates calculated along four transects re-occupied during the three cruises generally agreed across the five methods with two important exceptions. First, methods with pre-assigned Z int and/or N pre underestimated the NCP when the nitracline shoaled in the Laptev Sea and when high-nutrient shelf waters were advected northward from the East Siberian Sea shelf in 2015. In contrast, the methods that directly estimated both Z int and N pre did not suffer from this bias. These results suggest that assignment of N pre and/or Z int provides reasonable estimates of NCP, particularly averaged over larger spatial scales and/or longer time scales, but these approaches are not suitable for evaluating interannual variability in NCP, particularly in dynamic regions. Combining all methods across the three cruise years indicates NCP in the Laptev Sea and Lomonosov Ridge areas (10–11 g C m –2 ) was slightly lower than that north of Severnaya Zemlya (13 g C m –2 ) and in the East Siberian Sea (16 g C m –2 ).

A Steady Regime of Volume and Heat Transports in the Eastern Arctic Ocean in the Early 21st Century - A. V. Pnyushkov; I. V. Polyakov; G. V. Alekseev; I. M. Ashik; T. M. Baumann; E. C. Carmack; V. V. Ivanov; R. Rember (Frontiers in Marine Science, 2021)
Mooring observations in the eastern Eurasian Basin of the Arctic Ocean showed that mean 2013–2018 along-slope volume and heat (calculated relative to the freezing temperature) transports in the upper 800 m were 4.8 ± 0.1 Sv (1 Sv = 10 6 m 3 /s) and 34.8 ± 0.6 TW, respectively. Volume and heat transports within the Atlantic Water (AW) layer (∼150–800 m) in 2013–2018 lacked significant temporal shifts at annual and longer time scales: averaged over the two periods of mooring deployment in 2013–2015 and 2015–2018, volume transports were 3.1 ± 0.1 Sv, while AW heat transports were 31.3 ± 1.0 TW and 34.8 ± 0.8 TW. Moreover, the reconstructed AW volume transports over longer, 2003–2018, period of time showed strong interannual variations but lacked a statistically significant trend. However, we found a weak positive trend of 0.08 ± 0.07 Sv/year in the barotropic AW volume transport estimated using dynamic ocean topography (DOT) measurements in 2003–2014 – the longest period spanned by the DOT dataset. Vertical coherence of 2013–2018 transports in the halocline (70–140 m) and AW (∼150–800 m) layers was high, suggesting the essential role of the barotropic forcing in constraining along-slope transports. Quantitative estimates of transports and their variability discussed in this study help identify the role of atlantification in critical changes of the eastern Arctic Ocean.

Artificial Intelligence Technologies in the Diagnosis of Acute Lymphoblastic Leukemia and Minimal Residual Disease - V. G. Nikitaev; N. N. Tupitsyn; A. N. Pronichev; E. V. Polyakov; V. V. Dmitrieva; O. A. Chernysheva; I. N. Serebryakova; A. D. Palladina (Biomedical Engineering, 2021)

Effect of Glycyrrhizic Acid and Arabinogalactan on the Membrane Potential of Rat Thymocytes Studied by Potential-Sensitive Fluorescent Probe - Yuri I. Glazachev; Anna A. Schlotgauer; Viktor A. Timoshnikov; Polina A. Kononova; Olga Yu. Selyutina; Ekaterina A. Shelepova; Maxim V. Zelikman; Mikhail V. Khvostov; Nikolay E. Polyakov (The Journal of Membrane Biology, 2020)

Primary 3D Culture of Human Thyroid Follicle-Like Structures in Platelet Lysate-Based Gel - N. S. Sergeeva; V. A. Kirsanova; Yu. D. Khesuani; I. K. Sviridova; T. E. Skachkova; V. A. Mironov; A. P. Polyakov; A. D. Kaprin (Bulletin of Experimental Biology and Medicine, 2020)

Peculiarities of Pharmacokinetics and Bioavailability of Some Cardiovascular Drugs under Conditions of Antiorthostatic Hypokinesia - A. V. Polyakov; A. A. Svistunov; S. N. Kondratenko; I. V. Kovachevich; L. G. Repenkova; M. I. Savelyeva; V. G. Kukes (Bulletin of Experimental Biology and Medicine, 2020)

The study of the full spectrum of variants leading to hyperphenylalaninemia have revealed 10 new variants in the PAH gene - I. Kuznetcova; P. Gundorova; O. Ryzhkova; A. Polyakov (Metabolic Brain Disease, 2019)

Antimicrobial Activity of Supernatant of Lactobacillus plantarum against Pathogenic Microorganisms - Т. A. Danilova; A. A. Adzhieva; G. A. Danilina; N. B. Polyakov; A. I. Soloviev; V. G. Zhukhovitsky (Bulletin of Experimental Biology and Medicine, 2019)

Prognostic Risk Models for the Development of Cardiovascular Dysfunction in Adolescents with Essential Hypertension - A. S. Kosovtseva; Т. А. Bairova; L. V. Rychkova; V. M. Polyakov; L. I. Kolesnikova (Bulletin of Experimental Biology and Medicine, 2019)

In Vivo Experimental Study of Biological Compatibility of Tissue Engineered Tracheal Construct in Laboratory Primates - I. V. Gilevich; A. S. Sotnichenko; D. D. Karal-ogly; E. A. Gubareva; E. V. Kuevda; I. S. Polyakov; B. A. Lapin; S. V. Orlov; V. A. Porkhanov; V. P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2018)

Morphological Analysis of Biocompatibility of Autologous Bone Marrow Mononuclear Cells with Synthetic Polyethylene Terephthalate Scaffold - I. V. Gilevich; I. S. Polyakov; V. A. Porkhanov; V. P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2017)

Content of Circulating Extracellular DNA, Plasma Activities of Matrix Metalloproteinases, and Ultrastructure of the Myocardium in Hypothyroid Rats with Hypercholesterolemia - L. M. Polyakov; E. L. Lushnikova; A. A. Karpova; G. S. Russkikh; O. N. Poteryaeva; D. B. Nikityuk; L. M. Nepomnyashchikh; Zh. I. Belonogova; D. V. Sumenkova; R. D. Nepomnyashchikh; V. I. Pichigin (Bulletin of Experimental Biology and Medicine, 2015)

Redox Status as a Metabolic Stage, Integrating Emotional Pattern and Blood Pressure in Adolescents - L. I. Kolesnikova; Zh. V. Prokhorova; B. Ya. Vlasov; V. M. Polyakov (Bulletin of Experimental Biology and Medicine, 2014)

Heat loss from the Atlantic water layer in the northern Kara Sea: causes and consequences - I. A. Dmitrenko; S. A. Kirillov; N. Serra; N. V. Koldunov; V. V. Ivanov; U. Schauer; I. V. Polyakov; D. Barber; M. Janout; V. S. Lien; M. Makhotin; Y. Aksenov (Ocean Science, 2014)
A distinct, subsurface density front along the eastern St. Anna Trough in the northern Kara Sea is inferred from hydrographic observations in 1996 and 2008–2010. Direct velocity measurements show a persistent northward subsurface current (~ 18 cm s−1) along the St. Anna Trough eastern flank. This sheared flow, carrying the outflow from the Barents and Kara seas to the Arctic Ocean, is also evident from shipboard observations as well as from geostrophic velocities and numerical model simulations. Although we cannot substantiate our conclusions by direct observation-based estimates of mixing rates in the area, we hypothesize that the enhanced vertical mixing along the St. Anna Trough eastern flank favors the upward heat loss from the intermediate warm Atlantic water layer. Modeling results support this hypothesis. The upward heat flux inferred from hydrographic data and model simulations is of O(30–100) W m−2. The region of lowered sea ice thickness and concentration seen both in sea ice remote sensing observations and model simulations marks the Atlantic water pathway in the St. Anna Trough and adjacent Nansen Basin continental margin. In fact, the sea ice shows a delayed freeze-up onset during fall and a reduction in the sea ice thickness during winter. This is consistent with our results on the enhanced Atlantic water heat loss along the Atlantic water pathway in the St. Anna Trough.

Halocline water modification and along-slope advection at the Laptev Sea continental margin - D. Bauch; S. Torres-Valdes; I. Polyakov; A. Novikhin; I. Dmitrenko; J. McKay; A. Mix (Ocean Science, 2014)
A general pattern in water mass distribution and potential shelf–basin exchange is revealed at the Laptev Sea continental slope based on hydrochemical and stable oxygen isotope data from the summers 2005–2009. Despite considerable interannual variations, a frontal system can be inferred between shelf, continental slope and central Eurasian Basin waters in the upper 100 m of the water column along the continental slope. Net sea-ice melt is consistently found at the continental slope. However, the sea-ice meltwater signal is independent from the local retreat of the ice cover and appears to be advected from upwind locations. In addition to the along-slope frontal system at the continental shelf break, a strong gradient is identified on the Laptev Sea shelf between 122° E and 126° E with an eastward increase of riverine and sea-ice related brine water contents. These waters cross the shelf break at ~ 140° E and feed the low-salinity halocline water (LSHW, salinity S

Nature-inspired soluble iron-rich humic compounds: new look at the structure and properties - Tatiana A. Sorkina; Alexander Yu. Polyakov; Natalia A. Kulikova; Anastasia E. Goldt; Olga I. Philippova; Alina A. Aseeva; Alexey A. Veligzhanin; Yan V. Zubavichus; Denis A. Pankratov; Eugene A. Goodilin; Irina V. Perminova (Journal of Soils and Sediments, 2014)

Structural Changes in the Myocardium and Serum Lipid Spectrum in Experimental Hypercholesterolemia and Hypothyroidism - L. M. Nepomnyashchikh; E. L. Lushnikova; L. P. Polyakov; O. P. Molodykh; M. G. Klinnikova; G. S. Russkikh; O. N. Poteryaeva; R. D. Nepomnyashchikh; V. I. Pichigin (Bulletin of Experimental Biology and Medicine, 2013)

The Brain’s Error-Detecting Mechanism – a PET Study - M. V. Kireev; A. D. Korotkov; Yu. I. Polyakov; A. D. Anichkov; S. V. Medvedev (Neuroscience and Behavioral Physiology, 2013)

North Atlantic warming: patterns of long-term trend and multidecadal variability - Igor V. Polyakov; Vladimir A. Alexeev; Uma S. Bhatt; Evgenia I. Polyakova; Xiangdong Zhang (Climate Dynamics, 2010)

North Atlantic warming: patterns of long-term trend and multidecadal variability - Igor V. Polyakov; Vladimir A. Alexeev; Uma S. Bhatt; Evgenia I. Polyakova; Xiangdong Zhang (Climate Dynamics, 2010)

A New Genetic Variant of MDX Mice: Study of the Phenotype - L. I. Krivov; M. A. Stenina; V. N. Yarygin; A. V. Polyakov; V. I. Savchuk; S. A. Obrubov; N. V. Komarova (Bulletin of Experimental Biology and Medicine, 2009)

Modification and clearance of low density lipoproteins during the formation of endotoxin-lipoprotein complexes - Ya. Sh. Schvartz; L. M. Polyakov; M. I. Dushkin; E. N. Pivovarova (Bulletin of Experimental Biology and Medicine, 2008)

GH-1 gene splicing mutations: Molecular basis of hereditary isolated growth hormone deficiency in children - O. V. Fofanova; O. V. Evgrafov; A. V. Polyakov; V. A. Peterkova; I. I. Dedov (Bulletin of Experimental Biology and Medicine, 2006)

Development and Clinical Experience with a Computer Monitoring System Used at the Intensive Cardiological Care Unit - N. I. Kalyadin; V. A. Lemenkov; A. V. Korobeinikov; S. M. Perevozchikov; E. G. Odiyankov; A. N. Rodionov; V. F. Polyakov; S. M. Kotkov (Biomedical Engineering, 2002)

Effects of apolipoproteins C on oxidative phosphorylation in rat liver mitochondria - L. E. Panin; N. I. Shalbueva; L. M. Polyakov (Bulletin of Experimental Biology and Medicine, 2000)

Effects of apolipoproteins C on oxidative phosphorylation in rat liver mitochondria - L. E. Panin; N. I. Shalbueva; L. M. Polyakov (Bulletin of Experimental Biology and Medicine, 2000)